2009
DOI: 10.1021/jo901791k
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Investigation of Factors Influencing the Decarboxylation of Imidazolium Carboxylates

Abstract: A series of 1,3-disubstituted-2-imidazolium carboxylates, an adduct of CO(2) and N-heterocyclic carbenes, were synthesized and characterized using single crystal X-ray, thermogravimetric, IR, and NMR analysis. The TGA analysis of the NHC-CO(2)'s shows that as steric bulk on the N-substituent increases, the ability of the NHC-CO(2) to decarboxylate increases. The comparison of NHC-CO(2)'s with and without methyls at the 4,5-position indicate that extra electron density in the imidazolium ring enhances the stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
206
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(230 citation statements)
references
References 65 publications
21
206
1
2
Order By: Relevance
“…Louie and coworkers have now shown that the strength of binding CO 2 to the NHC fragment is tunable in a series of decarboxylation and transcarboxylation studies [33,34]. Thermal stability studies have yielded a series of data shown in Fig.…”
Section: C1-carriers In Nature: Folate Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Louie and coworkers have now shown that the strength of binding CO 2 to the NHC fragment is tunable in a series of decarboxylation and transcarboxylation studies [33,34]. Thermal stability studies have yielded a series of data shown in Fig.…”
Section: C1-carriers In Nature: Folate Chemistrymentioning
confidence: 99%
“…In Scheme 7, such binding is demonstrated to occur with a phosphine Lewis Base and a borane Lewis Acid. Catalytic reductions of CO 2 to methanolic species have been shown with the help of phosphine-borane (33) binding and catalysis [60,61] with a borane terminal reducing agent (32).…”
Section: Lewis-acid/base Activation and Catalysismentioning
confidence: 99%
“…For the catalytic reaction, a different reaction pathway can be assumed similar to the proposed mechanism in literature for the formation of isolable NHC [22,29,30] . For a catalyst with much lower basicity, e.g., as for the Al 2 O 3 used here, carbene formation was not observed.…”
Section: Resultsmentioning
confidence: 99%
“…The alkaline catalyst forms a stable N-heterocyclic carbene (NHC) ( 4 ) which can be isolated and purifi ed for further use (compare Scheme 2 ) [28,29] .…”
Section: Introductionmentioning
confidence: 99%
“…1630 to 1690 cm −1 depending on the N-substituents. 26,27 The 13 C MAS NMR spectrum of 2 shows a single set of resonances assignable to the ligand resonances. Most notably, two resonances at 156.1 and 145.0 ppm are assigned to the carbons of the NHC-coordinated CO 2 and the azolium C 2 respectively.…”
mentioning
confidence: 99%